OPTIMIZATION OF TURNING PARAMETERS FOR TITANIUM ALLOY TI-6AL-4V ELI USING THE RESPONSE SURFACE METHOD (RSM) - M.A., Sulaiman; C.H., Che Haron; J.A., Ghani; M.S., Kasim, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Titanium alloys are attractive materials due to their uniquely high strength–weight ratio, which is maintained at elevated temperatures. Due to the low machinability of titanium alloys, optimization of machining conditions is crucial. Uncoated carbide tool (CNGG 120408-SGF-H13A) was used to turn the titanium alloy Ti-6Al-4V ELI. In this study, the effects of cutting speed, feed rate, and depth of cut parameters were examined. Cutting-speed range of 120–220 m/min was used under flooded conditions. Response surface method (RSM) with a Box-Behnken design was utilized to set the 17 parameter runs. Analysis shows that cutting speed had the greatest effect on tool life, followed by feed rate and depth of cut. Meanwhile the feed rate was most significant factor for surface roughness, Ra of machined surface rather than cutting speed and depth of cut. Additionally, the optimum machining conditions were determined using RSM for both tool life and Ra to be a high cutting-speed of 220 m/min and a low depth of cut and feed rate of 0.4 mm and 0.1 mm/rev, respectively. Here the tool life gave 14.55 min for predicted value, but the validation thru experimental work produced 13.05 min, and the error about 10.65%. Moreover the surface roughness, Ra value for predicted was 0.529µm, meanwhile the validation gave 0.489 µm. This error was calculated to 7.56%.